Impaired Self-Other Distinction and Subcortical Gray-Matter Alterations Characterize Socio-Cognitive Disturbances in Multiple Sclerosis - Czekóová, Kristína; Shaw, Daniel Joel; Saxunová, Kristína; Dufek, Michal; Mareček, Radek; Vaníček, Jiří; Brázdil, Milan (Frontiers in Neurology, 2019)
Introduction: Recent studies of patients with multiple sclerosis (MS) have revealed disturbances in high-level components of social cognition, such as impaired mentalizing and empathy. The present study investigated this socio-cognitive profile in MS patients in more detail by examining not only affective mentalizing but also the performance on tasks measuring more fundamental components – namely, imitative tendencies and visual perspective taking – and any associated neuroanatomical alterations. Methods: We compared 43 patients with relapse-remitting MS with 43 age- and sex-matched healthy controls (HCs) on clinical characteristics (depression, fatigue), general cognitive functioning, and various aspects of social cognition; specifically, imitation, visual perspective taking, and affective mentalizing. Using voxel-based morphometry, we then explored relationships between these behavioral measures and patterns of grey-matter volume (GMV). Results: Patients exhibited significantly slower processing speed, poorer perspective taking, and less imitation compared with HCs. These impairments were related to reduced GMV throughout the left caudate nucleus, insula, putamen, and amygdala. Surprisingly, differences between the groups in affective mentalizing were not significant. Conclusion: Less imitation and poorer perspective taking indicate a cognitive self-bias when faced with conflicting self- and other-representations. This suggests that impaired self-other distinction, and an associated subcortical pattern of GM atrophy, might underlie the socio-cognitive disturbances observed in MS.